Restrictive business practices in international trade and the role of the World Trade Organization - Malaguti, Maria-Chiara (1998)
Looks at the question whether international multilateral co-operation should now be extended to deal with restrictive business practices. Examines existing instruments within the WTO that could be used to prevent government action. Seeks to determine whether to insert an explicit duty upon members to favour competition domestically or to adopt a fully-fledged competition code.